Нелинейная динамика развития организаций - Бушуев, Денис Антонович; Бушуев, Сергей Дмитриевич (НТУ "ХПИ", 2016)
Рассматривается нелинейное поведение организаций в проектах развития. Нелинейное поведение инициируется в процессах роста организаций и требует перестройки механизмов управления при выявлении дисфункций. Такая перестройка необходима в области мягких компонентов, определяющих организационную компетентность на уровнях менеджеров проектов, программ, портфелей проектов и руководителей офисов по управлению проектами. Важной составляющей стратегического развития организаций является предлагаемая концепция формирования и управления программами развития в контексте их жизненного цикла. При этом учитывается нелинейное поведение мягких компонентов системы и нарушения функциональных процессов организации.

The nonlinear behaviour of organizations in development projects is considered. The nonlinear behaviour is initiated in the growth of organizations and requires a restructuring of governance in identifying dysfunctions. Such a restructuring is needed in the area of soft components, determining the organizational levels of competence in the management of projects, programs, portfolios and heads of the Project Management Office. An important component of the strategic development of the organization is the proposed concept for formation and management of development programs in the context according their life cycle. It should take into account the non-linear behaviour of the soft components of the system and violation of functional processes of the organization. The specific management syndromes of projects and programs are considered. Such as syndromes time management project linked to the singular points of the project. This syndromes are "shift to the right", "point of no return", "braking at the end of the project" and others.
Non-liner dynamics of organization development
Keywords: цикл жизненный; бизнес-процесс; управление предприятием; мотивация; управление программами; портфель проекта; дисфункция; dynamics; complex systems; organization